2008
DOI: 10.1007/s11896-008-9030-y
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Resilience Training for Police: Psychophysiological and Performance Effects

Abstract: The objective of this study is to test the effects of police trauma resilience training on stress and performance during a critical incident police work simulation. Rookie police officers (N=18) participated in a randomized trial of a 10-week imagery and skills training program versus training as usual. Twelve months later, psychophysiological stress and police work performance were assessed during a live critical incident simulation. Training resulted in significantly less negative mood, less heart rate react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
199
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(211 citation statements)
references
References 43 publications
4
199
1
7
Order By: Relevance
“…Several studies on the effects of training programs among officers as described earlier (e.g., Arnetz et al 2009) showed promising results. However, a systematic review by Peñalba et al (2008) report psychological and psychosocial benefits found within small-scale studies, but stress the need for more well-designed studies to establish more thorough proof of efficacy of these programs.…”
Section: Mental Strength Trainingmentioning
confidence: 84%
See 4 more Smart Citations
“…Several studies on the effects of training programs among officers as described earlier (e.g., Arnetz et al 2009) showed promising results. However, a systematic review by Peñalba et al (2008) report psychological and psychosocial benefits found within small-scale studies, but stress the need for more well-designed studies to establish more thorough proof of efficacy of these programs.…”
Section: Mental Strength Trainingmentioning
confidence: 84%
“…To date, several intervention programs had been developed such as mental imaging training (Arnetz et al 2009), resilience training (Devilly and Varker 2013), and Heartmath® stress techniques (McCraty et al 2009). …”
Section: Mental Strength Trainingmentioning
confidence: 99%
See 3 more Smart Citations